The utility of cardiac magnetic resonance imaging in Kounis syndrome - Okur, Aylin; Kantarci, Mecit; Karaca, Leyla; Ogul, Hayri; Aköz, Ayhan; Kızrak, Yesim; Aslan, Sahin; Pirimoglu, Berhan; Aksakal, Enbiya; Emet, Mucahit (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Current diagnostic measurements used to assess myocardial involvement in Kounis syndrome, such as electrocardiography (ECG), cardiac enzymes, and troponin levels, are relatively insensitive to small but potentially significant functional change. According to our review of the literature, there has been no study using magnetic resonance imaging (MRI) on Kounis syndrome except for one case report. Aim : To identify the findings of dynamic contrast-enhanced magnetic resonance imaging (CE-MRI) in patients with Kounis syndrome (KS) type 1. Material and methods : We studied 26 patients (35 ±11.5 years, 53.8% male) with known or suspected KS type 1. The patients underwent precontrast, first-pass, and delayed enhancement cardiac MRI (DE-MRI). Contrast enhancement patterns, edema, hypokinesia, and localization for myocardial lesions were evaluated in all KS type 1 patients. Results : Contrast-enhanced magnetic resonance imaging demonstrated an early-phase subendocardial contrast defect, and T2-weighted images showed high-signal intensity consistent with edema in lesion areas. None of the lesion areas was found upon contrast enhancement on DE-MRI. The area of early-phase subendocardial contrast defect was reported as follows: the interventricular septum in 14 (53.8%) patients, the left ventricular lateral wall in 8 (30.7%), and the left ventricular apex in 4 (15.4%). Conclusions : Dynamic cardiac MR imaging is a reliable tool for assessing cardiac involvement in Kounis syndrome. Delayed contrast-enhanced images show normal washout in the subendocardial lesion area in patients with Kounis syndrome type 1.